Updates in the management of polycythemia vera and essential thrombocythemia - Prithviraj Bose (Therapeutic Advances in Hematology, 2019)
Polycythemia vera (PV) and essential thrombocythemia (ET) are both classic, relatively indolent, chronic Philadelphia-chromosome-negative (Ph − ) myeloproliferative neoplasms (MPNs) characterized by elevated blood counts, thrombotic as well as hemorrhagic tendencies, a variety of symptoms, cumulative risks of progression to myelofibrosis and transformation to acute myeloid leukemia over time, and long survival. Molecularly, PV is more homogenous, being driven by JAK2 mutations in virtually all cases, while ET can be JAK2-, CALR- , or MPL -mutated, as well as ‘triple negative’. Recent targeted next-generation sequencing efforts have identified other, nondriver gene mutations, some with prognostic relevance. Prevention of thrombotic and hemorrhagic complications continues to be the major focus of management, although symptoms are increasingly being recognized as a relatively unmet need, particularly in ET. Thrombotic risk stratification in PV is still based on age and history of thrombosis, while in ET, the additional contribution of JAK2 V617F to thrombotic risk is now well established. The associations of leukocytosis with clotting risk (in both conditions) and mortality (in PV) have drawn increased attention with the availability of ruxolitinib as a second-line treatment in PV. Similarly, there is a renewed interest in interferons with the emergence of ropeginterferon alfa-2b as a potential new frontline treatment option in PV. Drug development is more difficult in ET, the most indolent of the classic Ph − MPNs, but ruxolitinib is being studied. Triggering apoptosis via the p53 pathway through pharmacologic inhibition of human double minute 2 (and synergism with interferon) is a new, promising therapeutic strategy.